Main conditions of perinatal neurology: peculiarities of the out-patient follow-up - V. M. Studenikin (Лечащий Врач)
Main conditions constituting perinatal cerebral lesions in infants, are considered from position of pediatric neurologist’s out-patient check-ups and follow-up. Contemporary approaches to diagnostics and treatment of the above mentioned pathologies are discussed.